Pengembangan Sistem IoT Berbasis Sensor untuk Analisis Kesuburan Tanah pada Lahan Pertanian - Ery Muchyar Hasiri; Fahmi; Mohamad Arif Suryawan; Marselfa Nasir (Prosiding SISFOTEK, 2025)
The development of Internet of Things (IoT) technology has had a significant impact in various fields, including the agricultural sector. One of the main challenges in modern agriculture is the efficient and accurate measurement of soil fertility, including temperature, humidity, and nutrient content parameters such as nitrogen (N), phosphorus (P), and potassium (K). Manual measurements take considerable time, effort, and cost, and often result in less accurate data because they are subjective and not real-time. This research aims to design and build an IoT-based soil fertility measuring device that integrates NPK sensors, Soil Moisture sensors, and DHT22 sensors with ESP32 microcontrollers as the system control center. The methods used include hardware and software design, ESP32 programming using Arduino IDE, and integration with the Firebase platform for online data storage. It reads the soil conditions in real-time and displays the measurement results on the LCD, as well as transmitting data to a smartphone application over the internet. The test results show that the tool can distinguish fertile and infertile soil conditions well. In fertile soils, a temperature of 29°C, humidity of 89%, and NPK content of Nitrogen 20–23 ppm, Phosphorus 32 ppm, and Potassium 190–195 ppm, respectively. Meanwhile, in infertile soils, a temperature of 23–32°C, humidity below 75%, and a Nitrogen content of 12 ppm, Phosphorus 22 ppm, and Potassium 118–120 ppm. This system provides benefits in remote monitoring, resource efficiency, and increased agricultural productivity.